Teacher Strategies in Educating Children with Special Needs at SD Negeri 2 Blahkiuh in 2024 - I Made Sudarmayasa; Putu Beny Pradnyana; Desak Putu Anom Janawati (CV. Media Inti Teknologi, 2024)
This study aimed to determine the way teachers educate children with special needs. Children with special needs require different attention and approaches in terms of their needs. Focusing on physical, mental, emotional, and social aspects, they need additional attention and support to reach their full potential. This study is a qualitative study. The subjects of this study were Class Teachers of SD Negeri 2 Blahkiuh in 2024. The data collection method used an open interview instrument. The results of this study indicate the awareness of the majority of teachers towards the existence of children with special needs in their schools. Although most teachers understand the various types of special needs of children, there is a lack of experience in teaching children with special needs. However, teachers have shown various efforts to create an inclusive learning environment, such as the use of media, personal approaches, and adjustments to learning methods. Although some teachers have not received special training in teaching children with special needs, it is important for them to receive additional training to increase responsiveness to students' individual needs. The interview results also highlighted differences in school approaches regarding the integration of students with special needs into regular classes. In this context, it is important for schools to provide adequate training and support for teachers and adapt the curriculum and learning environment to ensure effective inclusion for all students, including those with special needs.